SOSIALISASI AMANDEMEN TERHADAP BATASAN USIA PERKAWINAN MELALUI UU NO.16 TAHUN 2019 TENTANG PERUBAHAN ATAS UU NO.1 TAHUN 1974 TENTANG PERKAWINAN - Vandita, Lalu Yoga; Taufik, Ahmad (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
The age limit for marriage in Indonesia has different regulations. In Law No. 1 of 1974 concerning Marriage, determines the age limit for marriage as 19 (nineteen) years for men and 16 (sixteen) years for women. However, in 2019, the government amended the age limit for marriage through Law No.16 of 2019 concerning Amendments to Law NO.1 of 1974 concerning Marriage. Marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. This activity uses the method of socializing Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage in strengthening legal awareness, especially knowledge related to statutory regulations in the field of family law, which is a very positive activity.